Réponses

  • Utilisateur Brainly
2014-03-12T08:34:54+01:00
Bonjour, 

Factoriser les expressions suivantes : 

A= (5x - 8)² + (5x - 8)
A= (5x - 8)(5x - 8) + (5x - 8) × 1
A= (5x - 8)(5x - 8 + 1)
A= (5x - 8)(5x - 7)


B= (2x + 5)² - 81
B= (2x + 5)(2x + 5) - 81
B= (2x + 5)(2x + 5) - 9 × 9
B= (2x + 5 - 9)(2x + 5 + 9)
B= (2x - 4)(2x + 14)
B= 2(x - 2) × 2(x + 7)
B= 4(x - 2)(x + 7)

Bonne journée! :)
2014-03-12T08:49:17+01:00

Factoriser : = transformer une somme en multiplication :

* = multiplié , par convention


A= (5x - 8)² + (5x - 8)
A= (5x - 8)*(5x - 8) + (5x - 8) * 1
A= (5x - 8)*(5x - 8 + 1)
A= (5x - 8)*(5x - 7)


B= (2x + 5)² - 81
B= (2x + 5)*(2x + 5) - 81

B= (2x + 5)*(2x + 5) - 9 * 9
B= (2x + 5 - 9)*(2x + 5 + 9)
B= (2x - 4)*(2x + 14)
B= 2(x - 2) * 2(x + 7)
B= 4*(x - 2)*(x + 7)